Priority Directions of Cooperation and Interaction of the Countries of the Eurasian Economic Union in the Scientific and Innovative Environment - ULYBYSHEV, Dmitriy; PETRENKO, Yelena; LENKOVA, Olga; AKENOV, Serik (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
In the article the authors reveal the positions of the countries of the Eurasian Economic Union, which are occupied in the global innovation index. They compare the parameters of citation of scientists of EurAsEC member countries; assess the opportunities for interaction between the countries of the Eurasian Economic Union from the position of SWOT-analysis. In addition, they present the results of an expert survey of scientists, entrepreneurs-innovators, employees of subjects of innovation infrastructure and state organizations responsible for supporting the development of scientific research and the introduction of innovations. The authors conclude that the main direction of cooperation should be joint work on innovative projects, and the key role of EurAsEC structures should be promoted by equalization of the conditions for the development of innovative firms in all countries and the formation of special interstate development institutions.